In Vitro Evaluation of the Microleakage in Bioflex Crowns Luted with Two Different Cements - Harsh S Baldawa; Mahesh Ramakrishnan (Journal of South Asian Association of Pediatric Dentistry)
Background: Microleakage, the penetration of oral fluids and bacteria at the tooth-cement-crown interface, is a primary cause of failure in dental restorations. It leads to secondary caries, pulp inflammation, and mechanical failure. Bioflex crowns, popular for their esthetic and functional benefits, require effective luting cements to minimize microleakage and ensure long-term success. This study evaluates the microleakage of different luting cements in Bioflex crowns using stereomicroscopy. Materials and methods: Forty-two extracted human mandibular second molars were randomly divided into two groups: group A (conventional glass ionomer cement, GIC) and group B (resin-modified glass ionomer cement, RMGIC). After cementation, the samples underwent thermocycling to simulate oral conditions, followed by immersion in 2% methylene blue dye for 24 hours. The teeth were then analyzed for microleakage at the tooth-cement-crown interface using a stereomicroscope at 10× magnification. Image analysis software was used to quantify the area and volume of dye penetration. Results: RMGIC showed significantly lower microleakage compared to GIC, with a marked reduction in both the volume and area of leakage. Statistical analysis revealed a significant difference between the two cements, indicating that RMGIC provides a better seal and stronger bond between the crown and tooth. Conclusion: RMGIC demonstrated superior resistance to microleakage, making it a more reliable option for luting Bioflex crowns compared to conventional GIC. This study underscores the importance of selecting appropriate luting cements to enhance the clinical longevity and success of dental restorations.